Coastal and inland salt-affected soils in Thailand : (Nodai Researcj Institute, 1987)
The first distinguishing features of this research was the emphasis on the application of both a common technique to cut off the capillary upward movement of sailine of\r acidifield groundwater and to enhance drainage of the surface qater. To accomplish this, coarse particles or lime gravels was laid below the surface soil layer in both field sites and organic and inorganic materials into the surface soil for the improvement of the soil fertility. the second research feature concerned its multidisciplinary approach which made reference to the fields of agricultural engineering, soil scinece, plant nutrition and ecology.